Financial Disclosure Transparency, Gender Equality, and Environmental Performance: Evidence from Energy Sector Companies - Yenny Wati; Yusrizal; Suyono; Fadrul; Febdwi Suryani (Jurnal Inovasi Akuntansi (JIA), 2026)
Purpose: This study investigates the effect of financial disclosure transparency on environmental performance and examines the moderating role of gender equality in energy sector companies. Method: The study employs a quantitative approach using panel data from energy sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. Data analysis is conducted using moderated regression analysis with EViews to test the proposed hypotheses. Findings: The empirical results indicate that financial disclosure transparency has a positive and significant effect on environmental performance, suggesting that higher transparency improves corporate accountability and environmental outcomes. Gender equality also has a positive effect on environmental performance, implying that gender-diverse leadership supports stronger environmental decision-making. Furthermore, the findings confirm that gender equality significantly moderates the relationship between financial disclosure transparency and environmental performance, strengthening the positive impact of transparency. Implications: From a theoretical perspective, this study extends stakeholder and legitimacy theories by incorporating gender equality as a governance mechanism that enhances the effectiveness of transparent disclosure. Practically, the results provide insights for regulators, investors, and corporate managers to improve disclosure quality and promote gender-inclusive governance. The novelty of this study lies in its moderated framework linking financial disclosure transparency, gender equality, and environmental performance in the Indonesian energy sector.